Refocusing Education Budgeting Policies for Public Accountability - Hamidi, Nurhasan (Proceedings International Conference on Education Innovation and Social Science, 2023)
There is a research gap in measuring the performance of educational institutions, but at the bottom there is a problem of how the level of effectiveness, economy, efficiency, economy and balance can be achieved. As a country that upholds democracy, accountability is an attribute of management accountability to the public. Accountability is currently under pressure from public sector organizations. The aim of this research is how to refocus the alignment of education policies in Indonesia in education budgeting so that the management of education funds is transparent and accountable. The study in this research uses a qualitative approach with a literature study. The results of the study show that the current most profitable focus on education budgeting is the vocational education level (SMK-Politeknik). The arguments are, first, that vocational/technical education is more expensive than academic education, but the implications for educational outcomes are more effective. Second, the need for more middle-level workers is required. Third, with the demographic bonus, the productive age population is considered to be a source of economic growth and innovation development. Fourth, the five important competencies that are currently developing are more likely to be achieved efficiently from vocational education (SMK-Politeknik). Fifth, currently the industry requires that workers must have competency certificates. The conclusion of this study is that the focus of developing the quality of education is on financing management policies because financial aspects have direct and indirect effects on the relationship between service quality and performance.